Detection of protein kinase activity specifically activated at metaphase-anaphase transition (The Rockefeller University Press, 1996)
We have previously reported that Ser13 and Ser34 on glial fibrillary acidic protein (GFAP) in the cleavage furrow of glioma cells are phosphorylated during late mitotic phase (Matsuoka, Y., K. Nishizawa, T. Yano, M. Shibata, S. Ando, T. Takahashi, and M. Inagaki. 1992, EMBO (Eur. Mol. Biol. Organ.) J. 11:2895-2902). This observation implies a possibility that there is a protein kinase specifically activated at metaphase-anaphase transition. To further analyze the cell cycle- dependent GFAP phosphorylation, we prepared monoclonal antibodies KT13 and KT34 which recognize the phosphorylation of GFAP at Ser13 and Ser34, respectively. Immunocytochemical studies with KT13 and KT34 revealed that the GFAP phosphorylation in the cleavage furrow during late mitotic phase occurred not only in glioma cells but also in human SW-13 and mouse Ltk- cells in which GFAP was ectopically expressed, thus the phosphorylation can be monitored in a wide range of cell types. Furthermore, we detected kinase activity which phosphorylates GFAP at Ser13 and Ser34 in the lysates of late mitotic cells but not in those of interphase cells or early mitotic cells. These results suggest that there exists a protein kinase which is specifically activated at the transition of metaphase to anaphase not only in GFAP-expressing cells but also in cells without GFAP.